2016
DOI: 10.1590/0102-6720201600s10008
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Profile of Patients Eligible for Bariatric Surgery

Abstract: Background: The psychologist who works in bariatric surgery has a role to receive, evaluate, prepare and educate the patient who will undergo the surgical procedure. Psychological evaluation becomes important in so far as allows us to obtain data on personal and familiar history and allow tracing of possible psychopathology. Aim: To collect data on psychological evaluations of patients in a bariatric surgery service of a public hospital in order to describe the psychological profile of patients in this service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 23 publications
0
3
0
11
Order By: Relevance
“…In addition to the above comorbidities, the high frequency of psychological diseases of obesity can lead to behavioral changes by the fact that these individuals are frequent targets of prejudice and discrimination 13 , 26 , 31 . Weight reduction and comorbidity was effective in decreasing depressive disorder in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the above comorbidities, the high frequency of psychological diseases of obesity can lead to behavioral changes by the fact that these individuals are frequent targets of prejudice and discrimination 13 , 26 , 31 . Weight reduction and comorbidity was effective in decreasing depressive disorder in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…This technique has the advantage of not generating problems of malabsorption because it does not change the contact of the food with the intestinal walls and with their respective digestive enzymes. Moreover, because it does not have digestive anastomosis, it offers a lower risk of postoperative complications compared to other techniques 3 , 6 , 7 , 15 , 20 , 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Only women were evaluated because there is a higher prevalence of bariatric surgeries in this population, which can be justified by the fact that females are more concerned with appearance and aesthetic issues when compared to males [ 21 ]. Furthermore, in the study carried out by Ribeiro et al [ 22 ] for example, it was found that 81% of the participants in the preoperative period of bariatric surgery were women and that they obtained higher scores in the classification of moderate anxiety compared to men, using the Beck Anxiety Inventory (BAI).…”
Section: Discussionmentioning
confidence: 99%
“…Na pesquisa realizada por Ribeiro et al (2016) com candidatos à cirurgia bariátrica também se deparou com uma população feminina em idade reprodutiva, economicamente ativa e 49% desempregados. Portanto, isso justifica a busca pelos benefícios da cirurgia bariátrica vislumbrando uma melhor condição de saúde para inserção no mercado de trabalho e planejamento familiar, como relatado pelos participantes desta pesquisa.…”
Section: Discussionunclassified